Riedel's Lobe of the Liver. Issue 3 (January 2015) - Savopoulos, Christos; Kakaletsis, Nikolaos; Kaiafa, Georgia; Iliadis, Fotios; Kalogera-Fountzila, Anna; Hatzitolios, Apostolos I.; Zapata., Eva
<x xml:space="preserve">Abstract</x> Abstract Riedel lobe of the liver is a simple anatomical variation, a downward tongue-like projection of the anterior edge of the right lobe of the liver to the right of the gallbladder with its typical case to be rare. We report the case of a 71-year-old woman with typical feature of a nonpalpable Riedel's lobe of the liver, as an incidental finding who was referred for reported hypergammaglobulinemia (22.7% [9%–19%]). Both features were attributed to a chronic inflammation because of an abscess in the right iliopsoas caused by infection due to bilateral hip replacement which underwent revision surgery. This was confirmed by her medical history, the imaging findings combined with elevated C-reactive protein, and by cross-reaction weak positive autoantibodies. Generally, knowledge or suspicion of Riedel's lobe of the liver is important, as it does not always remain clinically latent, as in our case, and it can be complicated by its torsion or hepatic tumors.